P123 Switching to biosimilars: what do patients think?. (23rd April 2022) - Coady, David; Parkin, Lindsay; Fairle, Louise; Smith, Andy
Abstract: Background/Aims: Newer 'biosmilars' come with a potential cost saving to the NHS. Switching of generic medicines has been studied (1) but not in the context of biologic drugs. We are interested in patients' views on switching to biosimilars. Will they have concerns and what can we do as Professionals to support them? Methods: A sample of 20 patients previously switched to a biosimilar were invited to a semi-structured face to face or telephone interview, lasting approximately 45mins. Interviews were recorded, anonymized and transcribed. Thematic analysis was undertaken by the research team using grounded theory (2). Results: 15 interviews took place until 'saturation'. Themes to emerge included: Trust: several patients mentioned 'trusting' someone they had an established relationship with, such as their consultant or specialist nurse. This would influence their decision to switch. Cost for NHS: awareness of costs to the NHS was discussed with a realisation that these are expensive drugs and there is a wider 'altruistic' need to switch to cheaper drugs when asked. But not all patients were happy. One patient felt 'pushed' into switching 'Cross, you know I have worked, my husband has worked, we've paid out National Insurances all out lives ⋯⋯ I was being pushed towards this cheaper version ⋯' Quality of delivery device: many comments were made on the quality of the delivery devices. ' It's just a bit more flimsy⋯'. Pre Switch training: some patients felt 'information' overload. Others did not read any extra information given. Others felt there was not enough support for the new device or training to use it. Preconceptions: several patients had preconceptions, that switching may create issues and described pre-switch anxiety: 'I was quite nervous about changing from one to another because I'd been perfectly fine with the one I was on ⋯⋯' Conclusion: Patients fell into two groups: 1) no particular anxiety about switching and 2) those with pre-switch anxiety. Pre switch anxiety seemed to be driven by prior experiences (reactions or ineffectiveness of prior medications). As the number of biosimilars increase it is likely that patients may be asked to switch multiple times. Confidence in the product and clinical support appear key to successful switching. We suggest a need for further research into this issue and intend to use the above themes in developing a questionnaire for wider sampling. Disclosure: D. Coady: Grants/research support; Biogen grant, N/A. L. Parkin: None. L. Fairle: None. A. Smith: None.